Pengaruh Debt to Asset Ratio dan Debt to Equity Ratio Terhadap Return On Asset Perusahaan Sektor Industri Makanan dan Minuman yang Terdaftar Di Bursa Efek Indonesia - Jurlinda Jurlinda; Juhaini Alie; Meilin Veronica (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to analyze the effect of debt to asset ratio (DAR) and debt to equity ratio (DER) on return on assets (ROA) in food and beverage industry companies listed on the Indonesia Stock Exchange (BEI). The data used in this study are secondary data obtained from the company's financial statements. The analytical method applied in this research is multiple linear regression method. The results prove that the debt to asset ratio (X1) has a significant negative effect on return on assets (Y). Debt to equity ratio (DER) (X2) has a significant positive effect on return on assets (ROA) (Y). This research is useful for companies to increase their return on assets through debt to asset ratio and debt to equity ratio).